Helicobacter pylori Infection in Dialysis Patients: A Meta-Analysis - Min Gu; Shuping Xiao; Xiaolin Pan; Guoxin Zhang (Gastroenterology Research and Practice)
Background. Infection with Helicobacter pylori contributes to the etiopathogenesis of various extragastrointestinal conditions, yet its etiological association with either symptomatic or asymptomatic dialysis patients remains inconclusive. Methods. Two researchers working independently conducted a literature search of the online databases PubMed, EMBase, ScienceDirect, and Cochrane Central Register of Controlled Trials to identify relevant articles to the end of 2012. Case-control and cross-sectional studies that met the inclusion criteria were included. Results. Fifteen studies involving 1237 dialysis patients and 1568 controls with normal renal function were included. Compared with normal controls, dialysis patients overall were associated with a relatively lower risk of H. pylori infection though not statistically significant. A significant inverse association was found between H. pylori prevalence and duration of treatments in those who were dialyzed >4 years (odds ratio 0.28; 95% confidence interval 0.22–0.36, ). No relationship between H. pylori status and duration of dialysis was observed in CRF patients. There were no significant differences in endoscopic features between patients and controls. Conclusions. Our meta-analysis found no evidence of a significant association between infection with H. pylori and dialysis overall, whereas long-term treatments of more than four years had a significant protective effect.